Septage treatment using pilot vertical-flow engineered wetlands system - Jong, V.; Tang, Fu Ee (2014)
This paper presents a two-staged, pilot-scale vertical flow engineered wetland-based septage treatment system (VFEWs), which was designed and constructed in Curtin University Sarawak Campus to determine the system efficiency in treatment of septage. The treatment system consists of storage tanks, vertical ﬂow wetlands, and a network of influent and effluent distribution pipes. The first stage of the VFEWs treatment system consists of three vertical flow wetlands placed in parallel to provide pre-treatment to raw septage to reduce solids and organic matters mainly by physical filtration and sedimentation processes. The percolate from the first stage is then further treated in the second stage, with four vertical flow wetlands, each with variation in operational regime and substrate (filter) type. The influences of various system and application-related parameters such as substrate material, presence of plants and plant types, and septage feeding practices (solid loading rate (SLR), batch and intermittent loading, and frequency of daily feeding) on pollutant removal efficiency were studied. Results from the first stage wetlands indicate that the removal of total solids and organic matter (BOD and COD) from the raw septage is promising (> 80%) at both SLR of 100 kg TS/m2.yr and 250 kg TS/m2.yr, respectively. However, a higher SLR decreased the average NH3-N removal efficiency. The findings on bed clogging assessment during the study period are also presented in this paper. Validation and expansion of these results are carried outwith ongoing assessments on the system performance.